Sentir que não fiz nada enquanto faço tudo: Mulheres artistas, Trabalho e Pandemia - Rosa, Lorena de Souza (2022)
This research proposes an analysis of the relationships between art, work and gender in the context of the Coronavirus (COVID-19) pandemic in Brazil. Taking home isolation as a starting point to think about the historical relationships between artistic production and isolation, it seeks to understand how the creative process of women artists behaves in these conditions. For that, oral interviews, bibliographic, journalistic and medical-scientific references were used. Through a qualitative and bibliographic historiographical approach, which sought to dialogue with different theoretical perspectives, from the Theory of Social Reproduction to analyses of contemporary isolation, including recent academic productions on the relationship between art and the pandemic developed at the height of the COVID-19 crisis between 2020 and 2021.